PENGARUH FORMULASI TEPUNG PANGAN LOKAL TERHADAP KARAKTERISTIK PRODUK FLAKES (SEREAL) : STUDI KEPUSTAKAAN - Ayu, Reliana Dwy Setia; Wahyuni, Sri; Faradilla, RH Fitri (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2021)
ABSTRACTThis review aimed to examine the characteristics of flakes products from several local food flour formulations. In addition, this review also aimed to determine the nutritional value composition of the flakes produced. The modification process of local food flour is done to improve the characteristics of the flakes produced. Flour from local food ingredients also produces starch properties that are better than wheat flour. The innovation process can be done through several additions or formulations, including using flour from corn, sweet potatoes, and fish. The results of the review show that the process of replacing or adding product formulations is proven to improve the characteristics of produced flakes to be better than commercial products, including improving the chemical composition and the characteristics of flakes products. Innovative flakes products from local food have the potential to be processed into healthy products.Keywords: Flakes, Local Food Flour, modifications, characteristics of flakesABSTRAKReview ini bertujuan untuk menelaah karakteristik produk flakes dari beberapa formulasi tepung pangan lokal. Selain itu, review ini juga bertujuan untuk mengetahui komposisi nilai gizi produk flakes yang dihasilkan. Proses modifikasi tepung pangan lokal dilakukan untuk untuk memperbaiki karakteristik produk flakes yang dihasilkan. Tepung dari bahan pangan lokal juga menghasilkan sifat tepung yang lebih baik dari tepung terigu. Proses inovasi dapat dilakukan melalui beberapa penambahan atau formulasi diantaranya adalah menggunakan tepung yang brasal dari jagung, ubi dan ikan. Hasil review menunjukkan bahwa proses penggantian atau penambahan formulasi produk terbukti dapat memperbaiki karakteristik produk flakes lebih baik daripada produk komersil, diantaranya adalah perbaikan komposisi kimia serta perbaikan karakteristik produk flakes. Produk flakes tepung inovasi dari pangan lokal memiliki potensi untuk diolah menjadi produk flakes sehat.Kata kunci: Flakes,tepung pangan lokal, modifikasi, karakteristik flakes